SIMULASI PENENTUAN TITIK PERTEMUAN SISTEM MANUFAKTUR BERTINGKAT PUSH DAN PULL - Chairul Saleh (Teknoin, 2006)
Production control systems for multistage manufacturing processes can be classified into push type (MRP) and pull type (JIT) systems. MRP and JIT system has its own unique advantages and disadvantages, and the advantages of both systems can be exploited to achieve better performance. A relatively new research trend associated with the MRP and JIT is to explore the possibility of hybrid system and to develop model for the integrated system. So, the choice of a production philosophy by a manufacturing company is important. The key components of overall profitability are holding cost inventory, WIP, set-up time and cost for missing due date on costumer order. The optimum lot-size associated with those of the key component. This paper presents an optimal lot-size production and integrated hybrid system with movable junction point between a Push sub-system and a Pull sub-system in production line using simulation approach. Using ARENA ® simulation software this model could solve the problem. The result can achieve minimum production cost with production output level for push system of 79 to 82 unit, decreasing WIP from 85.81 hour to 84.165 hour per cycle and decreasing waiting time in works station 2 to 5.Keywords : Push/Pull System, Lot-size, WIP, Manufacturing System